Maximizing Sales with Social Media and Email Marketing: Lessons from MSMEs in Sumenep Regency, Indonesia - Ghufrony, Ahmad; Ardini, Lilis; Mahaputra, Agung Pambudi (International Journal of Industrial Engineering, Technology & Operations Management, 2024)
In the modern digital landscape, micro, small, and medium enterprises face significant challenges in reaching and engaging their target customers. This quantitative research study examines the impact of social media and email marketing strategies on sales growth in Micro, Small, and Medium Enterprises in Sumenep District. It focuses on the effectiveness of social media and email marketing in the current digital era, where digital marketing strategies have become crucial for improving MSME performance and sustainability. MSME managers in the Sumenep district were surveyed using a specially designed questionnaire, and the data were analyzed using statistical methods to identify the relationships between social media use, email marketing, and MSME sales growth. The results reveal that social media strategies substantially influence MSME sales growth by increasing visibility, customer engagement, and brand awareness. However, email marketing has not significantly impacted MSME sales in the district, possibly due to limited adoption among MSME managers. This lack of adoption may be attributed to factors such as limited knowledge, resources, or the perceived effectiveness of email marketing among MSME owners in the region. The findings suggest that investing in social media marketing can be a viable strategy for MSMEs in Sumenep District to drive sales growth. Besides that, email marketing may require further education and support to increase adoption and effectiveness. This study provides insights that can help MSME owners and policymakers in Sumenep District develop more effective digital marketing strategies to enhance the performance and competitiveness of local businesses.